The Role of Leadership Style and Workload in Improving Employee Productivity - Farah Fadillah Amru; Maya Maya; Noveria Susijawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Employee labor productivity is a key component of organizational success, especially in manufacturing. This study aims to analyze the impact of leadership style and workload on employee labor productivity at PT Balagi. The research method used is quantitative with a survey approach by distributing questionnaires to 134. The results of multiple regression analysis show that leadership style and workload have a significant effect on employee productivity. Effective leadership styles, especially transformational and participative leadership, can increase employee participation and productivity. Conversely, high workloads can reduce work efficiency if not managed properly. This realization suggests that businesses must optimize management strategies and workload management to improve employee productivity and good attendance.